The Concept Of Ownership In Prophet’s Hadits: A Study Of The Principles Of Property Rights And Their Relevance To Contemporary Economics - Erniawati; Maghfirah; Asiqah Usman Ali (BAYAN: Jurnal Studi Islam dan Humaniora, 2025)
The gap between prophetic ownership principles in hadith and contemporary economic practices forms this research background. This study aims to analyze ownership concepts in hadith and explore their relevance to modern economics. The research employs qualitative methodology with descriptive-analytical approach through literature review. Findings reveal that ownership from hadith perspective constitutes trust (amanah) rather than absolute right. Three fundamental principles emerge: moral and social responsibility of owners, limitations preventing economic exploitation, and lawful wealth acquisition mechanisms. Implementation of these principles in modern economic systems manifests through Islamic banking, anti-monopoly regulations, and ethical digital economic development. The study formulates a tiered ownership model based on maqashid syariah with equitable redistribution mechanisms as alternative solution addressing global economic disparities.